2008
DOI: 10.1016/j.humpath.2008.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Follicular thyroid carcinoma with an unusual glomeruloid pattern of growth

Abstract: SummaryWe describe an uncommon thyroid tumor in a 56-year-old woman. The widely infiltrating, angioinvasive neoplasm, 5 cm in diameter, exhibited a peculiar architectural growth pattern characterized by follicles with round to oval epithelial tufts growing within, often supported by a fibrovascular core mimicking the renal glomerulus. Colloid-empty follicles, tubular or elongated, were lined by pseudostratified tall, columnar cells with clear cytoplasm. Nuclei were round to oval, with evenly distributed, sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
(25 reference statements)
2
10
0
Order By: Relevance
“…On the basis of differential expression of HBME-1 and galectin-3, in FTC expressing mutant RAS or PPFP, it was concluded that RAS and PPFP operate via distinct pathways (Nikiforova et al, 2003b). A novel and rare widely infiltrating, angioinvasive glomeruloid variant of FTC was shown to contain both RAS mutation and PPFP rearrangement (Cameselle-Teijeiro et al, 2008), but the contributions of both factors to this tumor’s growth phenotype are unknown. Finally, one study has shown that the co-existence of PPFP and aneuploidy was relatively more frequent among well differentiated tumors with 60% of FAs and 14% of FTCs harboring PPFP also exhibiting aneuploidy (Banito et al, 2007), suggesting that co-existence of PPFP and aneuploidy is not associated with a particularly aggressive phenotype (Banito et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of differential expression of HBME-1 and galectin-3, in FTC expressing mutant RAS or PPFP, it was concluded that RAS and PPFP operate via distinct pathways (Nikiforova et al, 2003b). A novel and rare widely infiltrating, angioinvasive glomeruloid variant of FTC was shown to contain both RAS mutation and PPFP rearrangement (Cameselle-Teijeiro et al, 2008), but the contributions of both factors to this tumor’s growth phenotype are unknown. Finally, one study has shown that the co-existence of PPFP and aneuploidy was relatively more frequent among well differentiated tumors with 60% of FAs and 14% of FTCs harboring PPFP also exhibiting aneuploidy (Banito et al, 2007), suggesting that co-existence of PPFP and aneuploidy is not associated with a particularly aggressive phenotype (Banito et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, glomeruloid features have also been described in single case reports of well differentiated papillary mesothelioma [18] and follicular thyroid carcinoma. [19] Taking in account the above all results and seeking the cause of the aforementioned morphology the authors realized that the tissue was improperly fixed. The specimen had been delayed for three days to reach the pathology department; it was cramped in a small pot with modicum fixative.…”
Section: Discussionmentioning
confidence: 99%
“…Glomeruloid variant of follicular thyroid carcinoma can be mistaken for cribriform-morular thyroid carcinoma, but lack of CDX2 and CD10-positive morules and absence of nuclear β-catenin positivity can help in this distinction. At variance with poorly differentiated thyroid carcinoma, glomeruloid variant of FTC was reported to have a low proliferative index and no necrosis [51]. When compared with a metastatic nephroblastoma (Wilms tumor), positivity for thyroglobulin and TTF-1 and only cytoplasmic and very limited positivity for WT1 distinguish this tumor from metastatic Wilms tumor.…”
Section: Follicular Tumors With Unusual Growth And/or Immunohistochemmentioning
confidence: 94%
“…Follicular thyroid neoplasms can display unusual growth pattern. A rare follicular thyroid carcinoma with an unusual glomeruloid pattern of growth has been reported [51]. This neoplasm was widely infiltrative with tumor nodules infiltrating the adjacent thyroid tissue, displaying several foci of vascular invasion.…”
Section: Follicular Tumors With Unusual Growth And/or Immunohistochemmentioning
confidence: 96%
See 1 more Smart Citation